FIRST PTEROSAUR POST-CRANIAL REMAINS FROM THE LOWER CRETACEOUS LOHAN CURA FORMATION (ALBIAN) OF PATAGONIA, ARGENTINA (Ameghiniana, 2019)
In this contribution, we present the first pterosaur post-cranial bone from the Lohan Cura Formation (Albian) of the Cerro de losLeones locality (Picún Leufú, Neuquén Province). The material is an incomplete left ulna, preserved in three dimensions, and composed of the proximal epiphysis and part of the diaphysis. The element shares several affinities with derived pterodactyloid pterosaurs, such as a diaphysis with a sub-oval cross-section, thin bone walls, pneumatic foramina in the dorsal surface of the proximal epiphysis and between the cotyles, and wingspan reconstruction indicating a medium-size specimen. An analysis of the microstructure allowed us to evaluate the ontogenetic stage of the specimen. The thin-section from the mid-shaft shows a wide and sub-circular medullary cavity, encircled by a thin cortical bone ring. In the innermost cortex, secondary lamellar bone forms a distinct and avascular endosteal layer, while the cortical layer is dominated by a well vascularized primary bone with coarse parallel fibers, as in other pterodactyloids. The presence of an avascular endosteal lamellar layer, an unremodeled cortical layer dominated by parallel-fibered bone, and a well ossified proximal epiphysis suggest that the specimen was an advanced juvenile or sub-adult with active-growth at the time of death. Considering the limited pterosaurian fossil record of Argentina, the new pterosaur specimen not only contributes to the reconstruction of the paleoecosystem of the Lohan Cura Formation in the central Neuquén Basin, but also improves our knowledge on the pterosaur taxonomic diversity during the Early Cretaceous of Patagonia.